(3GdcYc h GdHGQhO TF ef GdMQHs 2 - (3Jhajb, eMeOs ((3GdbGgQIs (3QjTI ddfTQs, 2023)
(3MGhd Cf JUOb, aeG LQi jUYH JUOjbg, QZe Cfg ef Gdeecf JhKjbg(B... (3GdLfOj GdPj LQi Ydi bOejg Nda GdOHGHI hgj JMGhd GdaQGQ efg, hGdadGM GdPj YHQ HLdHGHg bfGI GdShjS ZjQ YGHF HGdbfGHd GdJj JJSGbW Mhdg, hGdeRGQY GdPj nCnSnQ WjGQj GdYOh HaCSg GdJj jRQY HgG CQVg, hGdWHjH GdPj fnqXa CQVjI GdeSJTai, hGdegfOS GdPj bGO SjGQI GdUQa GdUMj, hGdaJGI GdJj CnqLdJ RhGLgG hJHQYJ HLgGRgG ef CLd LjTgG, hGdWadI GdJj hgHJ cd eG Jedc ddeLghO GdMQHj, hde Jcf Jedc Shi Kef YdHI SLGFQ hbWYI UGHhf(B...! (3ade Jcf MQkHG ddLfhO hMOge Ydi NW GdfGQ, hEfeG cGfJ eYQcI NGVgG TYH HCcedg, GbJSe eY GdebGJdjf QZja GdNHR hchH GdTGj, hGSJZfi Yf GdScQ, hGcJai HMdGhI GdfUQ(B"s
(3GdLRA GdKGfj dcJGH TF ef GdMQHs
Keywords: (3GdMQH GdYQHjI GdESQGFjdjIs; (3MQH CcJhHQ (B1973 (3es -- (3eUQs; (3eUQs -- (3JGQjNs -- (3GdYUQ GdMOjKs -- (3CfhQ GdSGOGJs